Correlation of Serum Sodium with Severity of Hepatic Encephalopathy (Medical Forum Monthly, 2024)
Objective: To study the correlation of serum sodium with severity of hepatic encephalopathy HE.Study Design: Cross sectional (Correlational) study.Place and Duration of Study: This study was conducted at Naseer Teaching Hospital Peshawar from October 2017 to September 2018.Materials and Methods: This study was conducted on 408 patients who were observed by using - 0.1411 of correlation coefficient between serum sodium (S.Na)and HE 95% confidence level and 80% power of test. More over non probability consecutive sampling was used for sample collection. The patients were collected from medical ward of NTH. After taking informed consent, clinical data were collected on a proforma designed for study. S.Na was evaluated in all cases of both groups and results were tabulated.Results: In this study mean age was 65 years with SD ± 0.315. Sixty-two percent patients were male and 38% patients were female. Mean S.Na (S.Na) level was 123 meq/L with SD ± 0.21. Five percent patients had severity of grade I, 39% patients had severity of grade II, 48% patients had severity of grade III and 8%o patients had severity of grade IV. Correlation of severity of HE with S.Na level was analyzed as all the 20 patients with severity of grade I had S.Na level ranged 131 -133 meq/L. All the 159 patients with severity of grade II had S.Na level ranged 126-130 meq/L. In 196 patients with severity of grade III, 45 patients had S.Na level ranged 126-130 meq/L while 151 patients had S.Na level ranged 120-125 meq/L whereas all the 33 patients with severity of grade V had S.Na level ranged 120-125 meq/L.Conclusion: Hyponatremia was a common feature in patients with cirrhosis and its severity increased with the severity of liver disease. The existence of S.Na concentration <135 mmol/L was associated with greater frequency of HE. It was also noticed that mote severe the hyponatremia, greater will be the grade of HE.